2022
DOI: 10.1212/wnl.0000000000200850
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-term Central Action of Botulinum Neurotoxin Treatment in Laryngeal Dystonia

Abstract: Background and Objectives:Laryngeal dystonia (LD) is isolated task-specific focal dystonia selectively impairing speech production. The first choice of LD treatment is botulinum neurotoxin (BoNT) injections into the affected laryngeal muscles. However, whether BoNT has a lasting therapeutic effect on disorder pathophysiology is unknown. We investigated short- and long-term effects of BoNT treatment on brain function in LD patients.Methods:A total of 161 subjects participated in the functional MRI study. Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The first, by Hok et al [ 94 ], focuses on cervical dystonia, which has been linked both to disrupted cerebellar function and acquired etiologies. The second, by O’Flynn et al [ 115 ], focuses on a task specific focal dystonia, whose underpinning etiology and associated networks have remained more enigmatic.…”
Section: Clues To Dystonia Pathophysiology Derived From Therapeutic I...mentioning
confidence: 99%
See 1 more Smart Citation
“…The first, by Hok et al [ 94 ], focuses on cervical dystonia, which has been linked both to disrupted cerebellar function and acquired etiologies. The second, by O’Flynn et al [ 115 ], focuses on a task specific focal dystonia, whose underpinning etiology and associated networks have remained more enigmatic.…”
Section: Clues To Dystonia Pathophysiology Derived From Therapeutic I...mentioning
confidence: 99%
“…Another recent study, performed by O’Flynn et al, furthers this conceptual framework by tackling a similar question in laryngeal dystonia [ 115 ]. In this study, the functional connectivity of 161 patients with laryngeal dystonia who had received short, intermediate, or long-term treatment with BoNT were examined using fcMRI.…”
Section: Clues To Dystonia Pathophysiology Derived From Therapeutic I...mentioning
confidence: 99%
“…What is more, BoNT can also be used for the treatment of some occupational dystonias, such as writer’s and musician’s cramps and stroke-related hemiplegia [ 186 ]. For laryngeal dystonia, characterized by spasmodic dysphonia, which manifests as either a laborious and tense sound that is interrupted by frequent articulatory interruptions and silent pauses, or a respiratory murmur, BoNT is also considered the treatment choice [ 187 ]. As for gastrointestinal, genitourinary, and sphincter disorders (such as achalasia, spasm of the sphincter of Oddi, and anal fissure [ 186 ]), the therapeutic efficacy of BoNT also acts on the spasm muscles in these organs [ 162 , 188 , 189 , 190 , 191 ].…”
Section: Clinical Applications Of Neurotoxinsmentioning
confidence: 99%
“…More recently, functional MRI studies have shown reduced activity in specific brain regions (left precuneus region) in LD patients successfully treated with BoNT compared with unsuccessfully treated and untreated patients. Moreover, subtype-specific regions of decreased activity were noted for the adductor (ADLD) (right thalamus) and abductor (ABLD) (left inferior frontal cortex) variants respectively [54]. Studies evaluating symptomatic improvement with BoNT treatment or peripheral stimulation show direct effects on muscle spindle as well as normalisation of cortical sensory organisation and function [43,47,55], implying correction of proprioceptive dysfunction as a mechanism for therapeutic response.…”
Section: Mechanism Of Action Of Botulinum Toxin In Ldmentioning
confidence: 99%